La difficile entreprise de réformer les médias en Tunisie - Larbi Chouikha (Communication)
Two months after the departure of former Tunisian President Ben Ali in January 2011, the Instance Nationale pour la Réforme de l’Information et de la Communication (INRIC) was set up to close the legislative and institutional gap created by the repeal of the repressive press laws and the abolition of the Ministry of Communication that regulated media activities in Tunisia. The author retraces the events leading up to INRIC’s decision to dissolve itself 18 months later. He attributes this decision to the singularity of the current transitional period in Tunisia’s history, which robs the government of any and all political will to act.